Implementasi Konsep Jaringan Bisnis dalam Meningkatkan Efisiensi Operasional Misala Gear Outdoor di Ciwidey Kabupaten Bandung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the implementation of business networks in improving operational efficiency in small and medium-sized enterprises (SMEs) operating in the outdoor equipment sector. Increasing public interest in outdoor activities has intensified competition among SMEs, requiring them to develop effective collaboration strategies to maintain operational sustainability. This research employs a qualitative descriptive approach with a single case study design conducted at Misala Gear Outdoor, an SME engaged in outdoor equipment rental and sales in Ciwidey, Bandung Regency. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using descriptive qualitative techniques. The results indicate that the implementation of business networks involving supplier partnerships, outdoor communities, tourism agents, and digital platforms contributes significantly to improving operational efficiency, particularly in inventory management, service delivery, and market reach. Moreover, business networks enable cost control, resource optimization, and service differentiation, which strengthen the enterprise’s competitive position. This study highlights the strategic role of business networks as an operational efficiency driver for SMEs in the outdoor industry and provides practical implications for SME managers in developing collaborative business strategies.